Are one-step aromatic nucleophilic substitutions of non-activated benzenes concerted processes?. Issue 35 (27th August 2019) - Domingo, Luis R.; Ríos-Gutiérrez, Mar; Chamorro, Eduardo; Pérez, Patricia
Abstract : Analysis of the mechanism of one-step SN Ar reactions of non-activated benzenes shows the presence of structures similar to those of Meisenheimer intermediates, thus accounting for the non-concerted nature of these reactions. Abstract : Aromatic nucleophilic substitution (SN Ar) reactions of non-electrophilically activated benzenes have been studied within the Molecular Electron Density Theory (MEDT) at the B3LYP/6-311+G(d) computational level. These reactions, taking place through a one-step mechanism, present a high activation Gibbs free energy, Δ G ≠ = 31.0 kcal mol −1, which decreases to 22.1 kcal mol −1 in the intramolecular process. A topological analysis of the electron localisation function along the reaction paths permits establishing the non-concerted nature of these SN Ar reactions. A series of unstable structures, with similar electronic structures to those of Meisenheimer intermediates, are characterised. The present MEDT study makes it possible to establish that even these one-step SN Ar reactions involving only two single bonds are non-concerted processes.